KOMPONEN KIMIA KAYU EKALIPTUS (Eucalyptus Urophylla S.T. Blake) HASIL PENJARANGAN DAN ALTERNATIF KEGUNAANNYA - Prabawa, Sigit Baktya (Universitas Nusa Bangsa, 2017)
Eucalyptus urophylla S.T. Blake in Indonesia is known as Eucalyptus, Popo, Ampupu and in abroad known as Timor white gum and Timor mountain gum. This species is native to Indonesia whose natural distribution includes Adonara, Alor, Flores, Lembata, Pantar, Timor, Wetar and Lombok. In Indonesia this species is recommended for Industrial Plantation Forests (IPF). In IPF activities, thinning is one of the important stages of activities to be carried out. The purpose of this study is to present technical information about the chemical components of thinning Eucalyptus plants which are around 4 years old in relation to their possible use. The results of this study showed that the extractive content of Eucalyptus wood dissolved in cold water, hot water, 1% NaOH and alcohol-benzene were 10.14%, 15.66%, 24.34% and 3.81% respectively. The content of lignin, hemicellulose, cellulose and holocellulose were 22.53%, 26.86%, 56.97% and 83.83% respectively. The difference in the position of the stem influences its extractive content where the higher position of thestem the lower the extractive content. This species is very suitable for pulping materials, both mechanical pulp, semi-chemical pulp and chemical pulp. In pulp and paper making, it is expected that this species would Â save the use of cooking chemicals or bleaching materials, resulting in high pulp yields and creating a good bond between fibers in the pulp or paper sheet. In the manufacture of particle boards, it is expected that this species would not become problems in resin hardening, internal breakage of the board due to volatile extractive internal gas pressure or dimensional stability. But this species is not suitable for cement boards.Â Keywords : Eucalyptus urophylla, Eucalyptus, Thining activity, IPF, Wood chemical component